Mercury accumulation rates in Caço Lake, NE Brazil during the past 20.000 years. (August 2017) - de Lacerda, Luiz Drude; Turcq, Bruno; Sifeddine, Abdel; Cordeiro, Renato Campello
Abstract: Total Hg, TC, TN, goethite and siderite distributions in sediment cores from two locations across Caçó Lake (Brazil) identified paleoclimate factors that had affected the Hg deposition in this shallow tropical lake and its relationship with past climate and basin processes. Concentrations and fluxes of Hg were maximum in the Last Glacial Maximum (LGM), with averages of 397 ng g −1 and 24.3 μg m −2 yr −1, respectively, decreasing during the Heinrich Stadial 1 (H1) and further during the Meltwater pulse 1A (MWP-1A). The higher values during LGM and H1 were strongly associated with dust deposition as observed in Greenland ice cores. After a period of lower values, there was a significant increase of concentrations and fluxes during the Younger Dryas (193 ng g −1 and 4.1 μg m −2 yr −1 ), still associated in part with dust deposition but also being influenced by the high volcanic activity of this period. Concentrations and fluxes decreased again to the lowest values during the Holocene from about 9500 to 2000 cal yr BP (114 ng g −1 and 1.25 μg m −2 yr −1 ). Analyses of 210 Pb dated shorter cores shows increasing Hg accumulation rates during the past century, larger than in other period in the past but could not evidence the influence of colonial gold mining as suggested by earlier studies. Highlights: First complete record of Hg deposition from the LGM to present in a tropical latitude. Deglaciation resulted in export of Hg to lakes by increasing runoff. Lowest Hg concentrations and fluxes occurred during the Melt Water Periods (MWP). Between MWP 1A and 1B, during the Younger Dryas, Hg deposition was similar to those during deglaciation. Volcanism contributed with relatively high Hg deposition between c.a. 5000 to 15, 000 years BP.